Gamma Rays and EMS Induced Chlorophyll Mutations in Grasspea (Lathyrus sativus L.) - Singh, Prabhat K.; Sadhukhan, R.; Kumar, V.; Sarkar, H. K. (International Journal of Bio-resource and Stress Management, 2019)
The present investigation was undertaken at department of Genetics and Plant Breeding, BCKV, Mohanpur Nadia (W.B.). A comparative study of frequency and spectrum of chlorophyll mutations induced by Gamma rays (400, 500 and 600 Gy), EMS (0.5% and 1%) and their combination treatments (400Gy+0.5% and 400Gy+1%) in M2 generation was done in three grasspea varieties viz., Nirmal, BioL-212 and Berhampur Local. The mutation frequency was estimated on M2 seedling basis. Broad spectrum of chlorophyll mutations like Albino, Xantha, Albo-Xantha, Xanthalba, Albo-Viridis, Virescence, Chlorina, Maculata, Albescence and Tigrina types could be scored from all the three varieties in M2 generation. Chlorophyll mutation frequency increases with increasing dose/ concentration of mutagen. Out of total chlorophyll mutation frequency (114.93%), Chlorina type exhibited maximum (17.93%) whereas Albescence type showed lowest frequency (2.16%). Total (Pooled) chlorophyll mutations frequency on variety basis indicated that out of total chlorophyll mutation frequency 43.06% (maximum) were produced in var. Nirmal, followed by BioL-212 (36.78%) and Berhampur Local (35.09%). Frequency of chlorophyll mutations on mutagen basis indicated that the gamma rays produced highest frequency (53.18%) followed by combined treatment of gamma rays and EMS (32.93%) where as chemical mutagen (EMS) produced lowest frequency (28.82%). The frequency and spectrum of chlorophyll mutations in grasspea are found to be both mutagen and variety dependent. The efficiency of different mutagens can be assessed through chlorophyll mutations which might be useful in selection of putative mutants in advanced generations.